Ethanol Production from Sago Palm Residue Pretreated with Two-Stage Chemical Process by Using Seed Sludge - Intanoo, Patcharee; Thammo, Nunticha (Journal of Food Health and Bioenvironmental Science, 2019)
The objectives in this work are to study the pretreatment of sago palm residue via two-stage chemical pretreatment process and to investigate the optimum fermented temperature for ethanol production by using seed sludge from wastewater treatment plant. The two-stage chemical pretreatment process with 0.5 %w/v sodium hydroxide followed by 0.26 %w/v sulfuric acid of sago palm residue was correlated with the removal of lignin and the disruption of cellulose structure, respectively. The pretreated sago palm residue was hydrolyzed with cellulase enzyme (Cellusoft ® CR conc) in order to convert cellulose and hemicellulose of sago palm residue to reducing sugar. The reduction of sugar was further fermented to produce ethanol by seed sludge at different temperature. From the study, it was found that the optimum hydrolysis time for pretreating sago palm residue was 72 hours. The pretreated sago palm residue via two-stage chemical pretreatment process gave a 49.63 % decrease in lignin and 81.57 % decrease in crystalline cellulose. It is suggested that the pretreated sago palm residue was easier to digest in reducing sugar by cellulase enzyme (Cellusoft ® CR conc) resulting in a fermented ethanol that was enhanced 3.2 times. Under a fermented temperature of 45°C, the process performance was more efficient in terms of the maximum ethanol yield.